2002
DOI: 10.1046/j.1471-4159.2002.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermine modulation of the glutamatenmda receptor is differentially responsive to conantokins in normal and Alzheimer's disease human cerebral cortex

Abstract: The pharmacology of the N-methyl-D-aspartate (NMDA) receptor site was examined in pathologically affected and relatively spared regions of cerebral cortex tissue obtained at autopsy from Alzheimer's disease cases and matched controls. The affinity and density of the [ 3 H]MK-801 binding site were delineated along with the enhancement of [ 3 H]MK-801 binding by glutamate and spermine. Maximal enhancement induced by either ligand was regionally variable; glutamatemediated maximal enhancement was higher in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…We have previously shown that certain conantokin peptides are weakly selective for the differing forms of NMDA receptor found in different regions of the AD brain (Ragnarsson et al 2002). Knowledge of the subunit composition should provide a convenient vehicle for further development by expressing the abundant and scarce combinations in a suitable recombinant system.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that certain conantokin peptides are weakly selective for the differing forms of NMDA receptor found in different regions of the AD brain (Ragnarsson et al 2002). Knowledge of the subunit composition should provide a convenient vehicle for further development by expressing the abundant and scarce combinations in a suitable recombinant system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent interesting study revealed that polyamines are able to modulate the mRNA stability of JunD, a growth-inhibitory protein in intestinal epithelial cells, through the RNA-binding proteins HuR and AUF1, thus providing new insight into the molecular functions of cellular polyamines [17]. Moreover, polyamines are able to modulate ligand-receptor interactions and functions, including estrogen/ER [18], the nuclear receptors/vitamin D receptor-interacting proteins [19] and the glutamate/N-methyl-D-aspartate receptors [20].…”
Section: Polyamine Synthesis and Functionsmentioning
confidence: 99%
“…Conantokin G (Con G), a small 17 amino acid peptide isolated from fish-hunting snail, Conus geographus, is the best-characterized conantokin (Olivera 1997), which exerts its in vivo effects through the functional inhibition of NMDA receptors (Layer et al 2004). The potential of Con G as a neuroprotective agent in ischemic and excitotoxic brain injury, neuronal apoptosis, and Alzheimer's disease has been reported (Dave et al 2003;Ragnarsson et al 2002;Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%